Characterization of the atmosphere during SEN2FLEX 2005 field campaign - Estelles, V; Molero, F; Gomez-Amo, J; Fortea, J; Pedros, R; Utrillas, M; Pujadas, M; Guanter, L; Martinez-Lozano, J (2008)
The European Space Agency carried out the Sentinel-2 and Fluorescence Experiment (SEN2FLEX) campaign in Barrax (Spain) during the summer of 2005, with the main objective of observe solar induced fluorescence signal using the AirFLEX airborne instrument over different vegetation targets in order to verify signal suitability for observations from space as proposed in the FLEX mission. A highly precise atmospheric correction is mandatory for adequate measurements of the AirFLEX instrument; thus a complete characterization of the atmosphere was programmed in SEN2FLEX in order to document the presence of atmospheric aerosols above the experimental area, as their effects represent the major source of uncertainty in atmospheric correction algorithms. In this work, an analysis of the atmospheric data is presented focusing on its eventual application to atmospheric correction of satellite imagery. Validation of Compact Airborne Spectrographic Imager (CASI) aerosol optical depth and columnar water vapor content retrievals has been included as an example of application to remote sensing products. A relevant feature was the arrival of a Saharan dust intrusion from 13 to 15 July, yielding the increase of aerosol optical depth at 550 nm from 0.1 to 0.5 because of changes in the vertical distribution of aerosols, with a transport layer located between 1.5 and 4 km. An accurate knowledge of these aerosol features will be relevant in future implementation of atmospheric correction code of the airborne and satellite hyperspectral imagery. Copyright 2008 by the American Geophysical Union.